2014
DOI: 10.1097/01.tp.0000435703.61642.43
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation Results of Completely HLA-Mismatched Living and Completely HLA-Matched Deceased-Donor Kidneys Are Comparable

Abstract: The influence of HLA mismatches on death-censored graft survival holds true for both deceased- and living-donor kidney transplantation. However, the relative risk of death-censored graft failure of a 2-2-2 mismatched living-donor kidney is comparable with that of a 0-0-0 mismatched deceased-donor kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
0
20
0
2
Order By: Relevance
“…In addition, the difference in impact of DSAs on graft survival between living and deceased donor transplant is likely not due to difference in either DSA strength (Table S7a) or immunization status, as there was no stronger effect of DSAs on graft survival in patients retransplanted with a living donor kidney, than in patients receiving a living donor kidney as first transplant with a much lower level of immunization (Table S8; Figure S1; Figure S4). However, it is known that graft survival rates of poorly HLA‐matched living donor grafts are superior to those of well HLA‐matched deceased donor grafts 16, 32. This can partially be explained by the prolonged CIT in deceased donors but also by inherent factors of the organ due to cardiovascular instability of the donor before nephrectomy, who may play a role 33.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the difference in impact of DSAs on graft survival between living and deceased donor transplant is likely not due to difference in either DSA strength (Table S7a) or immunization status, as there was no stronger effect of DSAs on graft survival in patients retransplanted with a living donor kidney, than in patients receiving a living donor kidney as first transplant with a much lower level of immunization (Table S8; Figure S1; Figure S4). However, it is known that graft survival rates of poorly HLA‐matched living donor grafts are superior to those of well HLA‐matched deceased donor grafts 16, 32. This can partially be explained by the prolonged CIT in deceased donors but also by inherent factors of the organ due to cardiovascular instability of the donor before nephrectomy, who may play a role 33.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that graft survival rates in patients who received a living donor kidney are higher than the rates in recipients of a deceased donor kidney 16. While recent large‐cohort studies of the impact of DSAs on graft survival have mainly focused on deceased donor transplants,17, 18, 19 the effect of SAB assay–detected DSAs on living donor transplants has not been studied in large cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Panel reactive antibody (PRA) best describes the degree of immunization and in multivariable analysis high levels are associated with graft failure censored for death. In multivariable analysis, the number of preceding renal transplants does not influence graft survival when PRA is present in the model (2).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the authors concluded that it is difficult to justify preferentially waiting for a well HLA‐matched DD kidney if there is an LD kidney available for transplantation, regardless of the level of HLA matching in the LD kidney. Furthermore, it has been shown in adults that the relative risk of graft failure of a fully mismatched LD kidney is comparable with that of a fully matched DD kidney …”
Section: Discussionmentioning
confidence: 99%
“…Secondly, potential LDs for pediatric patients are sometimes re- Furthermore, it has been shown in adults that the relative risk of graft failure of a fully mismatched LD kidney is comparable with that of a fully matched DD kidney. 23 The ultimate goal is clearly to achieve well HLA-matched LD kidney transplants for children, because these have the best renal allograft survival outcomes and produce the best long-term outcomes for patients. Further research is required to assess the impact of kidney waiting time on patient outcomes and the potential long-term consequences of poor HLA matching with implications for re-transplantation in children and adolescents due to HLA sensitization.…”
Section: Discussionmentioning
confidence: 99%